PENGAMANAN CITRA DENGAN ALGORITMA DIFFIE-HELLMAN DAN ALGORITMA SIMPLIFIED DATA ENCRYPTION STANDARD (S-DES) - ahmad Kamsyakawuni; Ahmad Husnan Fanani; abduh Riski (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2018)
Simplified Data Encryption Standard (S-DES) is a cryptographic algorithm whose data-disguise process is simple and fast enough compared to other algorithms. Because of its simplicity, the S-DES algorithm is vulnerable to statistical attacks when applied to imagery, so this study tries to minimize S-DES weaknesses in image data by modifying S-DES keys with Diffie-Hellman. Diffie-Hellman is one of the key generating algorithms and key exchange. This research uses image data that is RGB image and grayscale image. A modified S-DES key with Diffie-Hellman is then used to encrypt the image. This study also analyzed the security level of S-DES algorithm that the key has been modified with Diffie-Hellman.